PATIENT CHARACTERISTICS FACTORS ON THE QUALITY OF LIFE TYPE 2 DIABETES MELLITUS PATIENTS WITH INSULIN-BASED THERAPY - Lolita Lolita; Trimurti Andayani; Lutfan Budi Purnomo (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2013)
ABSTRACT Type 2 Diabetes mellitus is a chronic disease that can not be cured completely, will affect Health Related Quality Of Life (HRQOL). The purpose of this study was to determine the QOL of type 2 DM patients based on patient’s characteristic factors (age, gender, educational status) at Endocrinology Clinic Dr. Sardjito Hospital Yogyakarta. This study is a cross sectional study with descriptive method. Data are taken concurrently by interview and from medical records of patients who visited the Endocrinology Clinic Dr. Sardjito Hospital between July 2012 until March 2013. The inclusion criteria of patients include patients who visit during the study, no constraint in the language and not having a nervous breakdown, and willing to participate the study. The quality of life was measured by Diabetes Quality of Life Clinical Trial Quessionnaire (DQLCTQ). There are several statistical analysis used in this study. Mann Whitney for QOL analysis based on gender, educational status. Kruskall Wallis for QOL analysis based on patient’s age. The results of 137 patients known that gender (p value= 0,000) and education status (p value = 0,000) was significantly influence the average value of quality of life. Whereas, the patient’s age (p value = 0,530) was not significantly affect the average value of quality of life. Keywords: patients characteristics factors, quality of life, type 2 diabetes mellitus